Degradation of tartrazine dye using advanced oxidation process: Application of response surface methodology for optimization - Fetcia Jackulin; P. Senthil Kumar; Gayathri Rangasamy (Desalination and Water Treatment)
Among the azo dye, Tartrazine is widely used for most of applications like pharmaceuticals, cosmetics, food, etc. As the demand for dye application is increased, the disposal of dye is also increasing. However it is very difficult to cleave due to its stability. Different methods are available, but the Advanced Oxidation Process (AOP) is an emerging technique used for treating various contaminants. In this study, sulfate radical (SO4−.) based AOP was performed to degrade tartrazine dye using iron oxide (Fe3O4) nanoparticles (NP). This NP was synthesized using the co-precipitation method, analyzed by X-Ray Diffraction (XRD), revealed the crystalline structure of the material and the average size of the particle was 16.17 nm also High Resolution- Scanning Electron Microscope (HR-SEM) showed spherical and cube shape of the particles with agglomeration. Response surface methodology (RSM) was carried out to determine the optimum condition based on central composite design. The optimum conditions were found to be pH-5.34, time- 113.58 min, NP- 0.89 g, SPS- 15.40 mM, and predicted degradation efficiency - 97.22% which was correlated to the experimental value- 96.66% with minimal error. Application of SO4−. radical implied an efficient degradation due to the involvement of both SO4−. and hydroxyl (OH-.) radical. Excess formation of SO4−. radicals, Fe2+ was majorily responsible for suppressive degradation. The intermediate compound was identified from Gas Chromatography-Mass Spectrometry (GC-MS), proved the absence of parent dye and occurrence of degradation due to Fe3O4/PS system.